Prevention of irinotecan induced diarrhea by probiotics: A randomized double blind, placebo controlled pilot study. Issue 3 (June 2015) - Mego, Michal; Chovanec, Jozef; Vochyanova-Andrezalova, Iveta; Konkolovsky, Peter; Mikulova, Milada; Reckova, Maria; Miskovska, Vera; Bystricky, Branislav; Beniak, Juraj; Medvecova, Lenka; Lagin, Adela; Svetlovska, Daniela; et al.
Highlights Probiotics reduced grade 3–4 diarrhea after irinotecan based chemotherapy. Probiotics reduced all grades of diarrhea and enterocolitis compared to placebo. Patients on probiotics used less antidiarrheal drugs compared to placebo. Probiotics could reduce gastrointestinal toxicity of irinotecan based therapy.